How Do Landscape Structure, Management and Habitat Quality Drive the Colonization of Habitat Patches by the Dryad Butterfly (Lepidoptera: Satyrinae) in Fragmented Grassland? - Konrad Kalarus; Piotr Nowicki (PLoS ONE, 2015)
Most studies dealing with species distribution patterns on fragmented landscapes focus on the characteristics of habitat patches that influence local occurrence and abundance, but they tend to neglect the question of what drives colonization of previously unoccupied patches. In a study of the dryad butterfly, we combined classical approaches derived from metapopulation theory and landscape ecology to investigate the factors driving colonization from a recent refugium. In three consecutive transect surveys, we recorded the presence and numbers of imagos in 27 patches of xerothermic grassland and 26 patches of wet meadow. Among the predictors affecting the occurrence and abundance of the dryad, we considered environmental variables reflecting (i) habitat patch quality (e.g., goldenrod cover, shrub density, vegetation height); (ii) factors associated with habitat spatial structure (patch size, patch isolation and fragmentation); and (iii) features of patch surroundings (100-m buffers around patches) that potentially pose barriers or provide corridors. Patch colonization by the dryad was strongly limited by the distance from the species refugium in the region; there was a slight positive effect of shrub density in this respect. Butterfly abundance increased in smaller and more fragmented habitat patches; it was negatively impacted by invasive goldenrod cover, and positively influenced by the density of watercourses in patch surroundings. Nectar plant availability was positively related to species abundance in xerothermic grassland, while in wet meadow the effect was the reverse. We conclude that dryad colonization of our study area is very recent, since the most important factor limiting colonization was distance from the refugium, while the habitat quality of target patches had less relevance. In order to preserve the species, conservation managers should focus on enhancing the quality of large patches and should also direct their efforts on smaller and more fragmented ones, including those with relatively low resource availability, because such habitat fragments have an important role to play for specialist species.